2002
DOI: 10.1103/physreve.66.046613
|View full text |Cite
|
Sign up to set email alerts
|

Dipole radiation in a one-dimensional photonic crystal. II. TM polarization

Abstract: As in a recent paper [I. Alvarado-Rodríguez, P. Halevi, and Adán S. Sánchez, Phys. Rev. E 63, 056613 (2001); 65, 039901(E) (2002)], we study the power emitted by an oscillating dipole in a superlattice (SL) modeled by means of a periodic distribution of Dirac-delta functions (Dirac-comb SL). However, while in the aforementioned paper the radiation was restricted to the transverse electric (TE) polarization mode, here we focus our attention on the transverse magnetic (TM) mode. Employing the same methodology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…The temporal dispersion of the material can be used to realize dispersion compensation [20], pulse compression [21], pulse shaping [22], and optical delay [23]. The spatial dispersion of photonic crystals covers another set of applications including subwavelength imaging [24][25], beam shaping [26], controlling the radiation pattern [27][28][29], superprism-based demultiplexing [14], and diffraction-free propagation [30][31].…”
Section: Applications Of Dispersive Photonic Crystalsmentioning
confidence: 99%
“…The temporal dispersion of the material can be used to realize dispersion compensation [20], pulse compression [21], pulse shaping [22], and optical delay [23]. The spatial dispersion of photonic crystals covers another set of applications including subwavelength imaging [24][25], beam shaping [26], controlling the radiation pattern [27][28][29], superprism-based demultiplexing [14], and diffraction-free propagation [30][31].…”
Section: Applications Of Dispersive Photonic Crystalsmentioning
confidence: 99%
“…Several device ideas based on temporal dispersion of the material have been proposed, including dispersion compensation, 7 pulse compression, 8 pulse shaping, 9 and optical delay. 10 The controllable spatial dispersion in photonic crystals have been proposed for another set of applications such as subwavelength imaging, [11][12] beam shaping, 13 controlling the radiation pattern, [14][15][16] superprism-based demultiplexing, 6 and diffractionfree propagation. [17][18] We have previously demonstrated that the unique dispersive properties of Si-based PCs (i.e., superprism effect, negative diffraction, and negative refraction) can be combined to realize ultra-compact devices for spatial separation of different wavelength channels of an optical signal.…”
Section: Superprism-based On-chip Spectrometersmentioning
confidence: 99%
“…In [16], both infinite and finite crystals of planes were considered and their transmission and reflection properties were studied with the use of transfer matrix methods. The infinite crystal was again considered in [17,18,19,20] and named the 'Diraccomb superlattice'. Frequency-dependent emission rates were determined for several positions in the unit cell and both TE- [17,19] and TM-waves [18,20] were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The infinite crystal was again considered in [17,18,19,20] and named the 'Diraccomb superlattice'. Frequency-dependent emission rates were determined for several positions in the unit cell and both TE- [17,19] and TM-waves [18,20] were considered. The periodicity of infinite crystals makes that Bloch's theorem can be used in the analysis.…”
Section: Introductionmentioning
confidence: 99%